Facing treatment of non-urothelial bladder cancers in the immunotherapy era. (September 2020) - Grilo, I; Rodrigues, C; Soares, A; Grande, E
Graphical abstract: Highlights: Adenocarcinoma is the most common non-urothelial subtype of bladder cancer followed by squamous cell carcinoma and neuroendocrine tumors among others. Non-urothelial and urothelial variant bladder cancers generally exhibit an aggressive course with poor response to traditional treatments. These subtypes of bladder cancer represent rare diseases that might benefit from a broad range of therapeutic strategies including immunotherapy. Studies show that genetic aberrations, amplifications, and protein expression may herald potential drug targets for these uncommon cancers. Clinical trials including patients with rare forms of bladder cancer treated with checkpoint inhibitors are underway. Abstract: Non-urothelial Bladder Cancer (BC) and variants of urothelial carcinoma account for up to 25 % of all BCs. Given their heterogeneity, these entities are not well represented in clinical trials and treatment remains challenging. Checkpoint inhibitor therapy has shown a role in the treatment of urothelial BC. By contrast, robust evidence regarding its use in other histological types is lacking. We aimed to provide a comprehensive update of non-urothelial and variant urothelial BC, exploring the evidence for immune checkpoint inhibitor therapy. A detailed analysis of the literature was conducted regarding epidemiology, aetiology, diagnosis, prognosis, treatment and outcomes of these patients in the immunotherapy era. A growing body of evidence suggests that immune checkpoint inhibition might have a role to play in non-urothelial BC, similarly to what happened with urothelial carcinomas.